Metode Statistika Popular pada Skripsi Program Studi S.1 PAI UIN Walisongo Semarang 2021 - Dwi Yunitasari (LP3M Sekolah Tinggi Agama Islam Nahdlatul Wathan SAMAWA SUMBAWA BESAR, 2022)
The learning achievement of the Education Statistics course is students are able to understand and apply statistical methods in research using applications such as excel and SPSS, the problem is there are students who don’t understand statistical methods both in theory and practice. Empirical data on various statistical methods used in research are needed in increasing student competence. Therefore, this study aims to (1) identify the statistical methods used in research (2) Calculate the frequency of use of each statistical method. This research is quantitative research with descriptive statistics analysis. The research variable is the type of statistical method used in the undergraduate thesis of PAI UIN Walisongo Semarang students in the odd semester 2021/2022. Data collection is drawn by census. The data source used is the repository website of UIN Walisongo Semarang. Identification of the types of statistical methods in the PAI thesis shows that there are 57 theses in the odd semester 2021/2022, divided into quantitative research (10 theses) and qualitative (47 theses). In the thesis with quantitative research, there are 7 (seven) kinds of statistical methods, namely: Central tendention (10 theses), standard deviation (10 theses), simple linear regression (8 theses), frequency distribution table (6 theses) , bar graph (6 thesis); correlation analysis (5 thesis), and pie chart (1 thesis). This means that there is little interest in quantitative research in the PAI study program, and the most popular statistical methods are Central tendention, and standard deviation, while pie charts are less popular